PUBLIC SPEAKING ASN DALAM INOVASI PENGEMBANGAN PERUMAHAN MENGATASI KAWASAN KUMUH DI KELURAHAN SUKAMAJU KECAMATAN SAKO - Ardiansyah, Arif; Kazim, Eka Satria (Aktivasi: Jurnal Pemberdayaan Masyarakat, 2019)
The implementation of the Housing Development Program for the Community in Sukamaju Village, SakoDistrict, Kelurahan Sukamaju Regency is focused on factors, namely establishing a community housing system, developing efficient housing. The results showed that the implementation of the Housing Development Program for the Community in Sukamaju Village, SakoDistrict, Kelurahan Sukamaju Regency, had been realized well, this was seen from the large number of self-help housing stimulant assistance to improve the quality of houses to be habitable and the availability of basic housing facilities and infrastructure. , the availability of special houses, rental flats for Civil Servants and Police Members which were built in Sukamaju Village, but there are no rental flats for MBR yet.